Implementasi E-Commerce Clothing Line Menggunakan Metode Design Thinking dan System Usability Scale - Raihan Abdi Negoro; Agung Triayudi; Agus Iskandar (JURIKOM (Jurnal Riset Komputer), 2023)
Starting from the idea of wanting to make high quality jeans inspired by great vintage american clothing and vintage motorcycle culture and attitude, Carnivores soul is a clothing line store founded in 2014, which sells heavyweight selvedge denim made by skilled tailors and equipped with hardware good quality. During the observation stage of the Carnivores Soul website to users, there were several users who had difficulty and stopped for a moment when they wanted to sign in and sign up due to the placement of the forms next to each other. Then there is no product category which results in unstructured user experience functionality. The main purpose of making the Carnivores Soul e-commerce website by Pak Fadhil Aryananta is to make it easier for customers from abroad who want to order and buy products from Carnivores Soul. Relying on a website-based e-commerce platform, Carnivores Soul strives to provide the best experience in online shopping activities for users or customers. In order to provide users with the best shopping experience, carnivores soul wanted to redesign its website. The methodology used in this redesign process is the application of design thinking. Design thinking is a human-centred approach to solving problems and generating new innovations. The testing process is run to get feedback using the usability testing stage. This research shows the results of the development of the display design for the carnivores soul site which was carried out using the design thinking method as a design method and the System Usability Scale as a testing method. From the results obtained on the SUS score, a score of "79.6" was obtained which indicated that the carnivores soul website was declared Acceptable and included in the grade B category with a GOOD rating